A Remark on a Nonlocal-in-Time Heat Equation - Walker, Christoph (Comptes Rendus. Mathématique)
Schauder’s fixed point theorem is used to derive the existence of solutions to a semilinear heat equation. The equation features a nonlinear term that depends on the time-integral of the unknown on the whole, a priori given, interval of existence.